HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN PSYCHOLOGICAL WELL-BEING PADA ORANG TUA YANG MEMILIKI ANAK TUNAGRAHITA SEDANG - Starry Kireida Kusnadi; Nur Irmayanti; Husni Anggoro; Kemilau Senja Berlian Agustina (JURNAL PSIKOLOGI INSIGHT, 2021)
Abstract The purpose of this study was to see how the relationship between family support and psychological well-being of parents who have moderately retarded children. Family support is a form of interpersonal relationship that includes attitudes, actions and acceptance of family members, so that family members feel someone is paying attention. Psychological well-being is a condition in which individuals are able to accept themselves as they are, able to form warm relationships with others, have independence from social pressures, are able to control the external environment, have a meaning in life, and are able to realize themselves continuously. High family support will have a positive impact on psychological well-being. This research uses quantitative methods. The scale used is the family support scale adapted from the research of Meka Yusselda and Ice Yulia (2016), and the psychological well-being scale from Ryff's Scales of Psychological Well-being which was adapted from the research of M. Ilham Fahmy AM (2017). The subjects in this study were 30 parents. The results showed that there was a significant relationship between family support and psychological well-being. Thus, it can be concluded that the higher the family support, the higher the psychological well-being of parents who have children with moderate mental retardation and vice versa.  AbstrakTujuan penelitian ini untuk melihat bagaimana hubungan dukungan keluarga dengan psychological well-being pada orang tua yang memiliki anak tunagrahita sedang. Penelitian ini menggunakan metode kuantitatif. Subjek dalam penelitian ini adalah 30 orang tua Instrumen yang digunakan dalam penelitian ini adalah skala dukungan keluarga yang diadaptasi dari penelitian Meka Yusselda dan Ice Yulia (2016), dan skala psychological well-being dari Ryff’s Scales of Psychological Well-being yang diadaptasi dari penelitian M. Ilham Fahmy AM (2017). Hasil penelitian menunjukkan terdapat hubungan yang signifikan antara dukungan keluarga dengan psychological well-being. Dengan demikian, dapat disimpulkan bahwa semakin tinggi dukungan keluarga, semakin tinggi pula psychological well-being pada orang tua yang memiliki anak tunagrahita sedang dan begitupula sebaliknya.